(untitled) (Papeles, 2009)
Educational processes have evolved at a general level in their daily work involving technologies; the special education area of the Institut Pedagogic National has joined this process, which together with the Area of Technology and Computer Science have developed a project that involves Information and Communication Technologies (ict) in the teaching-learning process of students with permanent special educational needs. The project uses tic as a component for improving and strengthening the basic learning devices (bld), which are the fundamental basis for knowledge acquisition and learning of every human being. Within the search for information there are not theorical references to develop the unified bld, for that reason the research group developed tools for data collection and evaluation.